Inflation and companies’ performance: a crosssectional analysis - Ali, Maimunah; Ibrahim, Patmawati (American Scientific Publishers, 2018)
Inflation is a major problem in many countries because during inflation, the purchasing power of money declines as the prices of goods and services increase. The impact of inflation affects the profits by reacting on sales volume and also influencing the level of costs. Manufacturing companies play an important role and have large influence on the Malaysian economy for the past three decades because it contributes almost 80% of overall country’s export. Company’s performance can be indicated by the gross profits obtained from the comprehensive income statement of the company. Manufacturing companies need to be aware of the impact of inflation to sustain the manufacturing company’s performance. Therefore, the aim of this study is to analyze whether there is a significant impact of inflation on manufacturing companies’ performance in Malaysia. Cross-sectional study will be used in this study. Fifty manufacturing companies will be chosen based on the population. Cluster random sampling is going to be used in this study along with correlation analysis, to understand how changes in gross profit is affected by the rate of inflation. The finding of research shows that there is a positive relationship between gross profit and inflation rate. This indicates inflation in fact contributed to a higher earning in manufacturing companies instead of lowering profits